Perlindungan Hukum Hak Siar Liga Inggris atas Komersialisasi Nonton Bareng Tanpa Lisensi di Kafe Jakarta Selatan - Widya Rahmawati Asmara; Anne Gunawati; Rully Syahrul Mucharom (Gapenas Publisher, 2026)
The commercialization of English Premier League live broadcasts through public viewing activities in cafés without a license has become increasingly common and raises legal issues concerning the protection of broadcasting rights. This study aims to analyze the legal protection provided to PT EMTEK Tbk as the exclusive broadcasting rights holder of the English Premier League in Indonesia against unauthorized commercial public viewing activities in cafés in South Jakarta, as well as the legal consequences arising from such violations. This research employed a normative juridical method supported by empirical data obtained through interviews with representatives of PT EMTEK Tbk, the Directorate General of Intellectual Property (DJKI), café owners, and café customers. The findings indicate that preventive legal protection has been implemented through a licensing mechanism, while efforts to disseminate information and increase legal awareness among small business owners remain limited. Repressive legal protection is legally available through civil remedies, criminal sanctions, and dispute resolution mechanisms; however, their implementation is still constrained by the complaint-based nature of copyright offenses and limited enforcement capacity. The legal consequences of unauthorized commercial public viewing are normatively regulated under the Copyright Law and the Broadcasting Law, although their application in practice has not yet been carried out consistently in the cafés examined in this study.